Tree Species of Wet Tropical Forests Differ in Their Tissue Biochemistry and Effects on Soil Carbon Dynamics - Russell, Ann E.; Marek, Rachel F.; Olk, Daniel C. (Frontiers in Forests and Global Change, 2021)
Given the hypothesized effects on soil organic matter (SOM) of polyphenols in plant tissues, differences among tree species in their biochemical composition could influence the turnover and accrual of SOM in various ways. The extent to which the biochemical composition of leaf and fine-root tissues differ among tropical tree species, and the effects on soil dynamics, are largely undocumented, however. We used cupric oxide analyses of plant tissues and soil in long-term, replicated, mono-dominant 15-yr-old plantations at La Selva Biological Station, Costa Rica, to test for differences among six tree species. We related these results to companion studies in this experimental site to evaluate relationships between interspecific differences in tissue biochemistry and SOM dynamics. Newly senesced leaves and fine roots of the six species differed in their concentrations of three lignin-derived families of phenols, the cinnamyls, syringyls and vanillyls (P <0.0001 for all tests). Cinnamyl and syringyl phenols in soil differed significantly among species (p = 0.0408, 0.0071, respectively), whereas vanillyl phenols did not (p = 0.83). The degree of decomposition of syringyl and vanillyl phenols in soil also differed (p = 0.0015, 0.0027 respectively), as evidenced by the ratio of carboxylic acid to aldehyde compounds, based on the concept that carboxylic acids are a common by-product of oxidative decomposition of lignin by microorganisms. In our study in a single site, i.e., the same soil type, climate, and growth form of vegetation, total phenols in soil ranged from 5 to 21 mg g-1 organic carbon (OC) across the 20 plots, and the endpoints were both broad-leaved evergreen species; even the means across species, 7–12 mg g-1 OC, covered half the range of values reported in another study across a broad latitudinal range of sites. This study’s tree species differed in traits that influenced at least four factors that explained their differential effects on SOC pools: (1) Fine-root detrital inputs; (2) Fine-root syringyl concentrations; (3) Soil pH; and (4) Macroaggregate structure. This trait-based approach provides a process-based understanding of how trees species influence SOC dynamics, and the consequences for ecosystem properties, under land-use change that involves shifts in species composition.